A two-dimensional nanopatterned thin metallic transparent conductor with high transparency from the ultraviolet to the infrared - Du, Qing Guo (2013)
The optical properties of a two-dimensional nanohole patterned aluminum thin film in hexagonal lattice are studied. The transmission dip can be moved out from the visible range by manipulating the lattice constant. The resulting nanopatterned thin film is demonstrated to exhibit a high transparency in a wide wavelength range. The origins of the transmission dip and the transmission drop are explained. For constant resistance, thicker films with a larger filling ratio lead to better transmittance in the visible range. Angular response of the nanopatterned metallic film is also analyzed, and transmittances using several other metals are compared.